2022
DOI: 10.1186/s13756-022-01059-1
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of poverty as risk factors for antimicrobial resistant organisms in Canada: a structured narrative review

Abstract: Background Few studies have assessed the relationship between poverty and the risk of infection with antimicrobial resistant organisms (AROs). We sought to identify, appraise, and synthesize the available published Canadian literature that analyzes living in poverty and risk of AROs. Methods A structured narrative review methodology was used, including a systematic search of three databases: MedLINE, EMBASE and Web of Science for articles pertainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…45 Furthermore, some food handlers may truncate the course of therapy because of their inability to pay for the full course of medication. 45,46 The use of antibiotics for less period of time than is required, can exert selective pressure on bacterial populations which contributes to their resistance. 44,45 Resistance to beta-lactams and fluoroquinolones must be of great concern as they are preferred to aminoglycosides for the treatment of serious infections because of their high efficacy and low toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…45 Furthermore, some food handlers may truncate the course of therapy because of their inability to pay for the full course of medication. 45,46 The use of antibiotics for less period of time than is required, can exert selective pressure on bacterial populations which contributes to their resistance. 44,45 Resistance to beta-lactams and fluoroquinolones must be of great concern as they are preferred to aminoglycosides for the treatment of serious infections because of their high efficacy and low toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is often within the first year that the decline in AMR carriage happens [27, 28] and unfortunately, we did not have enough samples from the first year of stay in Denmark to explore this in more detail. Finally, different determinants for SES have been found to be linked with higher risk of AMR [30, 31] however as previously discussed we did not have access to a good proxy for SES such as education level. Our results are not generalizable to the whole migrant population in Denmark since we only included family‐reunited migrants and refugees.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review from 2018 studied the impact of poverty on colonisation and infection with drug-resistant organisms and found that in high income countries crowded living conditions, lack of education and low income were associated with carriage/ infection with AMR organisms [30]. Another review from 2022 on poverty and social determinants for health as risk factors for AMR organisms in Canada found an increased prevalence among indigenous groups and found higher income to be associated with a lower prevalence of MRSA [31]. Previous studies have also pointed to international travel as a risk factor for increased resistance [3,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors may contribute to this observation. This may be driven by a high burden of medical conditions in lower-income communities in Canada (( 9 )), including infections (( 10 )). Antibiotic use may be linked to lower vaccination rates with various vaccines in low-income communities (( 11 , 12 )).…”
Section: Discussionmentioning
confidence: 99%